SeedCast mobile app - CGIAR Research Program on Rice (2018)
Innovative mobile app was launched in May 2018 to estimate seed demand for rice varieties in Odisha, India. The app will be piloted in the pre-Kharif season of 2018 in Odisha, is available on Google Play Store and is expected to have an upgraded version in future.